Differential activity of nelarabine and clofarabine in leukaemia and lymphoma cell lines - Styczyński, Jan; Kołodziej, Beata; Rafińska, Beata (Contemporary Oncology/Współczesna Onkologia, 2009)
Although the efficacy of nelarabine and clofarabine has been extensively studied in acute lymphoblastic leu-kaemia (ALL) in vitro and in vivo , less is known about their possible role in other haematological malignancies. The aim of this study was to perform an analysis of in vitro drug sensitivity of nelarabine and clofarabine in lymphoblastic lymphoma and myeloid leukaemia cell lines. Six cell lines were used for the study of in vitro drug sensitivity: two ALL (CCRF-CEM and Jurkat), two lymphoblastic lymphoma cell lines (Raji and Daudi), acute promyelocytic leukaemia (HL60) and chronic myeloid leukaemia (K562) cell lines. In vitro drug resistance was tested by the MTT assay. When compared to ALL cell lines, relatively good in vitro activity of clofarabine and nelarabine in both B-cell lymphomas was found. In vitro activity of both new purine analogues was favourable in comparison to cytarabine, fludarabine and cladribine activity. Drug sensitivity profiles of Raji and Daudi cell lines were comparable to each other, although overall, Raji cell line was less drug sensitive. There was good activity of clofarabine and nelarabine against HL60 cells, while K562 cell line was resistant to most of the tested drugs. Drugs used in high-dose therapy before haematopoietic stem cell transplantation, such as busulfan, etoposide, treosulfan and cyclophosphamide, presented good activity, when application of high doses during this procedure was taken into account. In conclusion, these results support the hypothesis of relatively good in vitro activity of nelarabine and clofarabine in tested B-cell lymphoma and HL60 cell lines.